EFFECTIVE USE OF ATM WITH SECURITY - Kumar, Shiv; shrama, Shrawan kumar; kumar, Awanit (IJRDO -Journal of Computer Science Engineering, 2015)
ATM (automated teller machine) is a new generation banking system. ATM is most usablefriendly machine. The main objective of this paper is to enhance more Security to ATM users’ as criminaloffence occurs more due to miss use of ATM. Since ATM have lack of Security we have interoduced fewobtion to reduce risk and miss use of ATM card by developing Thumb impression Security option withoutany need of hardware just only by upgrading software and second obtion is to changing the criteria oflimits of cash withdrawal and the third proposal is to make ATM Eco-friendly i.e. cash deposit can bemake by ATM only this will reduce the rush and save the Bankers’ time and no need to fill form for cashdeposition it will save paper.